CD40L Expression Allows CD8+ T Cells to Promote Their Own Expansion and Differentiation through Dendritic Cells - Tay, Neil Q.; Lee, Debbie C. P.; Chua, Yen Leong; Prabhu, Nayana; Gascoigne, Nicholas R. J.; Kemeny, David M. (Frontiers in Immunology, 2017)
CD8+ T cells play an important role in providing protective immunity against a wide range of pathogens and a number of different factors control their activation. Although CD40L-mediated CD40 licensing of dendritic cells (DCs) by CD4+ T cells is known to be necessary for the generation of a robust CD8+ T cell response, the contribution of CD8+ T cell-expressed CD40L on DC licensing is less clear. We have previously shown that CD8+ T cells are able to induce the production of IL-12 p70 by DCs in a CD40L-dependent manner, providing some evidence that CD8+ T cell-mediated activation of DCs is possible. To better understand the role of CD40L on CD8+ T cell responses, we generated and characterized CD40L-expressing CD8+ T cells both in vitro and in vivo. We found that CD40L was expressed on 30-50% of effector CD8+ T cells when stimulated and that this expression was transient. The expression of CD40L on CD8+ T cells promoted the proliferation and differentiation of both the CD40L-expressing CD8+ T cells and the bystander effector CD8+ T cells. This process occurred via a cell-extrinsic manner and was mediated by dendritic cells. These data demonstrate the existence of a mechanism where CD8+ T cells and DCs cooperate to maximize CD8+ T cell responses.